Non-Alcoholic Fatty Liver Disease Molecular Bases, Prevention and Treatment - Valenzuela, Rodrigo (IntechOpen, 2018)
Nonalcoholic fatty liver disease (NAFLD) with a prevalence of 20-30% worldwide is characterized by the buildup of fat in the liver (liver steatosis) with no or little alcohol consumption. Its principal causes are modern diet and occidental lifestyle. It is characterized by metabolic disturbances such as insulin resistance, inflammation, and oxidative stress, considered as the hepatic manifestation of metabolic syndrome. There is no effective drug therapy for this disease; therefore, lifestyle interventions remain as the first-line treatment. Nevertheless, the adherence rates to this type of treatment are very low, so great efforts are focused at finding novel therapeutic agents for the prevention of hepatic steatosis and its progression. This book presents a systematic and comprehensive revision about NAFLD, highlighting its epidemiological and molecular aspects, as well as its prevention and treatment.